IMPACT OF HABITAT SHIFTING ON FISHERY OF HILSA IN TAPTI ESTUARY - SHARMA, A P; Bhaumik, U; Mukhopadhyay, M K; Shrivastava, N P; ROSHITH, C M (Journal of the Inland Fisheries Society of India, 2020)
Clupeids happen to be significant component of open water fisheries in India. The group includes a number of species, among which Tenualosa besides quantitative importance has economic significance for the fishers and the entrepreneurs. In Indian sub-continent, hilsa is represented by three species viz. Tenualosa ilisha, Tenualosa toli and Hilsa kelee. These species differ in pattern of distribution and habitat requirements. Tenualosa ilisha makes annual breeding run to major Indian river systems on east and west coasts while the other two species inhabit mainly the marine-coastal waters of west coast and occasionally encountered in the east coast region. In proportional contribution, T. ilisha figures higher than the combined share of T. toli and H. kelee in overall hilsa fishery of the country (Jhingran, 1998). In growth scale T. ilisha grows maximum to 614 mm and 4.250 kg (CIFRI, 2011). While T. toli attains 525 mm and 1.5 kg, H. kelee remains further smaller in size. So far, there is no record of commercial appearance of all the three species of Tenualosa from any estuarine system of the country